A Half-Century of Heterotopic Heart Transplantation in Mice: The Spearhead of Immunology Research - Yin, Decheng; Dewald, Oliver; Peng, Xiangyu; Nie, Wenlong; Rong, Song; Dudziak, Diana; Lehmann, Christian; Hörning, André; Fu, Jian (Transplantology, 2024)
Since the success of solid organ transplants, such as human kidneys, livers and hearts, from the 50s to the 60s in the last century, the field of organ transplantation has progressed rapidly. Mainly due to modifications in surgical operation techniques and improvements in immunosuppressive therapy regimes, organ survival time can now be greatly prolonged. This progress has also been dependent upon the availability of appropriate animal models for organ transplantation. Therefore, the mouse heart transplantation model has developed into an irreplaceable research model for solid organ transplantation, providing indelible contributions to the field. In this review, we will provide an overview of the technical developments in murine heart transplantation, as well as its historical and current role for alloimmune research. Further, we will describe its current fields of application and its scientific achievements before we discuss potential future applications.
CRIS-Team Scopus Importer:2025-02-04
Keywords: heterotopic heart transplantation; immunology; murine transplantation